The employment of gamification towards excellence in police services management - Sarifah Putri Raflesia; Taufiqurrahman Rusdy; Dinda Lestarini; Firdaus Firdaus; Dinna Yunika Hardiyanti (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Gamification is a motivation and psychological-oriented approach which aims to boost user participation and engagement. It is commonly applied to business process and information systems which need outcomes improvement such as educational system, customer relationship management, human resource management system, health information system, so forth. The main purpose of gamification is using game elements to non-game purpose in order to motivate users. Unfortunately, building gamification system is not similar to build general software because developer needs to identify considerable psychology aspects and also engage other expertise. In this research, gamification framework and its implementation are proposed which took police department as research object. We present gamified-police management system development framework to build the gamified-police management system and its implementation in order to gain police engagement and public trust.